2016
DOI: 10.1016/j.cortex.2016.03.017
|View full text |Cite
|
Sign up to set email alerts
|

Visual mismatch negativity (vMMN): A review and meta-analysis of studies in psychiatric and neurological disorders

Abstract: The visual mismatch negativity (vMMN) response is an event-related potential (ERP) component, which is automatically elicited by events that violate predictions based on prior events. VMMN experiments use visual stimulus repetition to induce predictions, and vMMN is obtained by subtracting the response to rare unpredicted stimuli from those to frequent stimuli. One increasingly popular interpretation of the mismatch response postulates that vMMN, similar to its auditory counterpart (aMMN), represents a predict… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

8
88
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 119 publications
(99 citation statements)
references
References 296 publications
(353 reference statements)
8
88
1
2
Order By: Relevance
“…The vMMN is considered to be the visual counterpart of the earlier-discovered auditory MMN (Naatanen, et al, 1978), and has been similarly used to investigate a range of phenomena including sensory memory/change detection (Czigler et al, 2002), perceptual discrimination (Tales & Butler, 2006), stimulus repetition effects (Amado & Kovacs, 2016), and perceptual expectations (Stefanics et al, 2014). The magnitude of the visual mismatch response differs between healthy and clinical samples across a wide range of psychiatric and neurological disorders (reviewed in Kremlacek et al, 2016), as has also been found for the auditory MMN (reviewed in Naatanen et al, 2014). Figure 1.…”
Section: Introductionmentioning
confidence: 99%
“…The vMMN is considered to be the visual counterpart of the earlier-discovered auditory MMN (Naatanen, et al, 1978), and has been similarly used to investigate a range of phenomena including sensory memory/change detection (Czigler et al, 2002), perceptual discrimination (Tales & Butler, 2006), stimulus repetition effects (Amado & Kovacs, 2016), and perceptual expectations (Stefanics et al, 2014). The magnitude of the visual mismatch response differs between healthy and clinical samples across a wide range of psychiatric and neurological disorders (reviewed in Kremlacek et al, 2016), as has also been found for the auditory MMN (reviewed in Naatanen et al, 2014). Figure 1.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, new studies investigating vMMN in patients with psychiatric disorders have been conducted (for review see Kremláček et al, 2016). For example, a previous study has shown that deviant motion direction could elicit a reduction of vMMN signals in patients with schizophrenia, indicating the impairment of early processing of visual information (Urban et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…To assess the effect of distance on violated regularities, we analysed the visual mismatch negativity (vMMN) component of the ERPs. The vMMN is elicited by deviant visual stimuli within the sequence of physically or categorically equivalent stimuli, and by stimuli‐violated complex sequential regularities (for reviews, see Czigler, ; Kimura, Schröger, & Czigler, ; Kremlaček et al., ; Stefanics, Kremlácek, & Czigler, ). Investigating the effect of spatial attention on vMMN may specify the effectiveness of automatic processes in predictive coding theory in the visual modality.…”
Section: Introductionmentioning
confidence: 99%